تأثير التبادل الحراري بين جدران الأسطوانة والهواء على عمل الضواغط المكبسية - اسبر منى (Latakia University Journal -Engineering Sciences Series, 2019)
The research aims to find mathematical equations describing the process of heat exchange between the walls of cylinder and air, and the effect of this exchange on the volumetric productivity of the compressor based on Fourier theory of heat transfer. The results of the calculations showed that the absorbent air is subject to the effect of roller walls, and this effect is not the same for the different parts of the cylinder. The temperature fluctuates rapidly in the interior layers. On the outside surfaces, the temperature is equal to zero for all parts of the cylinder. The interrelationships between efficient working energy Q and adipatic energy attributed to free air were reached. The comparison of active action with adipatetic work was calculated by classical method. The calculated work according to this method increases the adipativity by 19% for the compressors with double compression. يهدف البحث إلى إيجاد معادلات رياضية توصف عملية التبادل الحراري بين جدران الأسطوانة والهواء، وتبيِّن تأثير هذا التبادل على الإنتاجية الحجمية للضاغط وذلك بالاعتماد على نظرية فورييه في انتقال الحرارة. أظهرت نتائج الحسابات أن الهواء الممتص يخضع لتأثير جدران الأسطوانة، وهذا التأثير ليس واحداً لمختلف أجزاء الأسطوانة. وإنَّ تذبذب الحرارة يضمحل بشكل سريع في الطبقات الداخلية، أما على السطوح الخارجية فالحرارة تساوي الصفر لكل أجزاء الأسطوانة. تمَّ التوصل إلى العلاقة المتبادلة بين طاقة العمل الفعالة وطاقة العمل الأدياباتية المنسوبة إلى الهواء الحر. أظهرت مقارنة العمل الفعال بالعمل الأدياباتي المحسوب بالطريقة الكلاسيكية، حيث أنَّ العمل المحسوب وفقاً لهذه الطريقة يزيد عن العمل الأدياباتي بنسبة 19% للضواغط ذات الانضغاط المضاعف.